Analysis of the technical and organizational capabilities of helicopters for the deployment of mobile ropeways based on airmobile rope units - Shatunova E.A.; Lagerev I.A. (Научно-технический вестник Брянского государственного университета)
Mobile ropeways based on airmobile rope units are a new constructive type of cargo and cargo-passenger ropeways for the rapid deployment of transport and overloading activities in hard-to-reach areas and high-altitude territories. The article provides a detailed analysis of the technical and organizational capabilities of the key method for delivering the necessary main and auxiliary technological equipment to the place of operation for these mobile ropeways — cargo transportation using transport and multi–purpose helicopters. Possible modifications of Russian helicopters are considered and based on the analysis of their technical characteristics (dimensions of cargo compartments, carrying capacity, practical range), recommendations for their use are made based on the required overall dimensions and weight of airmobile rope units. The necessity of using a method of transporting equipment mainly using an external load sling system is shown, the conditions for using transportation in the helicopter cargo hold are considered. Four possible technological variants of using a helicopter to carry out an operation for the delivery of airmobile rope units and related equipment to the place of the proposed deployment of a mobile ropeway, depending on the permissible distance between the points of loading and mantling of equipment, are proposed and analyzed.